If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 1) + 4 = -9(x + -8) + -5 Reorder the terms: 8(1 + x) + 4 = -9(x + -8) + -5 (1 * 8 + x * 8) + 4 = -9(x + -8) + -5 (8 + 8x) + 4 = -9(x + -8) + -5 Reorder the terms: 8 + 4 + 8x = -9(x + -8) + -5 Combine like terms: 8 + 4 = 12 12 + 8x = -9(x + -8) + -5 Reorder the terms: 12 + 8x = -9(-8 + x) + -5 12 + 8x = (-8 * -9 + x * -9) + -5 12 + 8x = (72 + -9x) + -5 Reorder the terms: 12 + 8x = 72 + -5 + -9x Combine like terms: 72 + -5 = 67 12 + 8x = 67 + -9x Solving 12 + 8x = 67 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 12 + 8x + 9x = 67 + -9x + 9x Combine like terms: 8x + 9x = 17x 12 + 17x = 67 + -9x + 9x Combine like terms: -9x + 9x = 0 12 + 17x = 67 + 0 12 + 17x = 67 Add '-12' to each side of the equation. 12 + -12 + 17x = 67 + -12 Combine like terms: 12 + -12 = 0 0 + 17x = 67 + -12 17x = 67 + -12 Combine like terms: 67 + -12 = 55 17x = 55 Divide each side by '17'. x = 3.235294118 Simplifying x = 3.235294118
| 2(5m-3)=4m+30 | | 6x-2=2x-6 | | y=-7(6)+8 | | 5x-3x-8= | | 4-2(5x+5)= | | 26+x=x+23+12-(14+x) | | 3-2(8x+4)= | | f(3)=21x+11 | | x(6x+7)=3 | | 2x^2-4+3=x^2-2x+11 | | 15-3n=12 | | -11f=7(1-2f)5 | | y=20-0.06x+0.0002x^2 | | 4-(7*x)=59 | | 4-7*x=59 | | 11-(x+3)= | | 300(14-x)+800x=6.200 | | -5(r+2)=-81 | | 4(x+2)+6= | | 12-5*x=-33 | | -11.6h+11.55=-12.7h | | -9.1c+19.02=-14.3c+11.74 | | 21x-8=5(4x+5)-17 | | -5(r+2)=81 | | -1/2q-4=9 | | 20+4y=40 | | 5(10-2n)=70 | | 8(x+15)=7 | | 1/5q-49 | | 6(2g-1)=13 | | 4(g+4)=2(4-g) | | 4x+4=7y |